DETERMINAN KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR - Astakoni, I Made Purba; Utami, Ni Made Satya (Jurnal Riset Akuntansi (JUARA), 2019)
The objectives of this study are: Analyzing the effect of liquidity on dividend policy; Analyzing the effect of company Size on dividend policy; Analyze the effect of debt policy on dividend policy. The population in this study are all Cement Sector Manufacturing companies whose shares are listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling so that two companies were appointed based on the 2012-2017 financial statements. Data analysis techniques used the Partial Least Square (PLS) approach. Based on the results of testing the hypothesis obtained; The first hypothesis; which states that there is a positive significant effect between liquidity on dividend policy. The results of the analysis find negative and insignificant coefficients. This means that liquidity has no significant effect on dividend policy so the first hypothesis cannot be accepted. Second hypothesis; which states there is a significant positive effect between company Size on dividend policy. The results of the analysis find coefficients and are not significant. This means that company Size does not have a significant negative effect on dividend policy, so the second hypothesis cannot be accepted. Third hypothesis; which states that there is a significant negative influence between debt policy on dividend policy. The analysis found positive and not significant coefficients. This means that debt policy does not have a significant effect on dividend policy so that the third hypothesis cannot be accepted.